Tinjauan Yuridis Kompilasi Hukum Islam tentang Hak Warisan Anak Hasil Hubungan di Luar Nikah antara Tenaga Kerja Wanita dengan Majikannya - Rahmat Vijay Bengal; Kasuwi Saiban; Wika Yudha Shanty; Fadilla Lailawaty (University of Merdeka Malang, 2021)
The large number of Indonesian workers who work abroad is one of the largest foreign exchange contributors in the country, but in practice, many problems arise for Indonesian workers who work abroad, one of which is the rape of female workers by their employers to cause children. from the results of the extramarital relationship. This study uses a normative juridical approach. This approach focuses on examining literature materials such as legislation and other relevant sources. This research examines how the compilation of Islamic law reviews the status and inheritance rights of children resulting from extramarital relations between female workers and theiremployers. The results of this study are children from the results of extramarital relations between female workers and their employers only have a family relationship with their mother and their mother’s family and do not have a family relationship with their biological father and the family of their biological father.